1997
DOI: 10.1103/physrevb.55.14872
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamical properties of small polarons

Abstract: On the basis of the two-site polaron problem, which we solve by exact diagonalization, we analyze the spectral properties of polaronic systems in view of discerning localized from itinerant polarons and bound polaron pairs from an ensemble of single polarons. The corresponding experimental techniques for that concern photoemission and inverse photoemission spectroscopy. The evolution of the density of states as a function of concentration of charge carriers and strength of the electron-phonon interaction clear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 26 publications
9
123
0
3
Order By: Relevance
“…(2)), we can consider the grains as isolated entities with very weak intergrain coupling and a typical Fermi energy of a grain is much smaller than the bulk Debye energy, the so called anti adiabatic regime [44].…”
Section: Fig 2 Important Crossover Lines Derived From Many Experimentsmentioning
confidence: 99%
“…(2)), we can consider the grains as isolated entities with very weak intergrain coupling and a typical Fermi energy of a grain is much smaller than the bulk Debye energy, the so called anti adiabatic regime [44].…”
Section: Fig 2 Important Crossover Lines Derived From Many Experimentsmentioning
confidence: 99%
“…It is worth to note that traditional variational approaches to the Holstein polaron problem uses the localized state (11) where only the on-site operator U (i) k (n) is applied. Thus we introduce in the expression of the trial wave-function the nearest-neighbor displacement operators U (i) k (n + 1) and U (i) k (n − 1), in order to take into account the dependence of the hopping integral on the relative distance between two adjacent ions.…”
Section: Variational Approach Vs Exact Diagonalizationmentioning
confidence: 99%
“…In particular it has been shown that the self-trapping process, which lead to the formation of polarons, is not a phase transition, but just a continuous crossover with no broken symmetry. 7 In the case of the Holstein model, 8 where quantum vibrations interact locally with the electrons, the crossover from large to small polaron has been extensively studied by several numerical techniques [9][10][11][12][13][14][15] and variational approaches. [16][17][18] In particular all the ground state properties of the Holstein model can be described with great accuracy by a variational approach 18 based on a linear superposition of Bloch states that describe weak and strong coupling polaron wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…In the weak-coupling (adiabatic) limit, one expects (from scaling arguments) a quasi-free electron behaviour for D > 1, while in a 1D system the carrier state becomes polaronic at arbitrary small λ ("large" polaron). Previous exact diagonalization (ED) work has concentrated on the 1D case [8][9][10][11][12]21,[13][14][15][16][17], where, however, the calculations were limited to either very small clusters, rather weak EP coupling (λ < 1) or to the adiabatic limit (ω o = 0). On the other hand, the most interesting effects will be expected if the characteristic electronic and phononic energy scales are not well separated (λ ∼ 1; α ∼ 1).…”
Section: Introductionmentioning
confidence: 99%